The Effect of Selective Renal Parenchymal Clamping during Laparoscopic Partial Nephrectomy on Early Postoperative Renal Function: A Preliminary Report - Nozaki, Tetsuo; Morii, Akihiro; Fujiuchi, Yasuyoshi; Fuse, Hideki (Urology Journal, 2014)
<!--[if gte mso 9]> Normal.dotm 0 0 1 202 1156 ???? 9 2 1419 12.0 <![endif]--><!--[if gte mso 9]> 0 false 10 pt 0 2 false false false $([\{£¥‘“????????????? !%),.:;?]}¢°’”‰′″?????????????????????????????????? <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:????; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0mm 5.4pt 0mm 5.4pt; mso-para-margin:0mm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-ascii-font-family:Century; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"?? ??"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Century; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-font-kerning:1.0pt;} --> <!--[endif] --> <!--StartFragment--> Abstract Purpose: A major concern when performing laparoscopic partial nephrectomy (LPN) is potential postoperative renal dysfunction. The objective of this study was to compare the effects of LPN with selective renal parenchymal clamping (SRPC) (LPNSRPC) and LPN using microwave tissue coagulation (MTC) (LPNMTC) on postoperative renal function. Materials and Methods: This study included 12 patients (5 men and 7 women) who underwent LPNSRPC (n = 6) or LPNMTC (n = 6) for exophytic tumors. Renal scanning with technetium- 99m diethylenetriaminepentaacetic acid (Tc-99m DTPA) was performed preoperatively and postoperatively at 1 month in all patients. Results: The mean tumor size, surgical duration, and intraoperative blood loss were similar in both groups. In the LPNMTC group, although not significant, the mean postoperative glomerular filtration rate (GFR) values in the affected kidneys were decreased compared to the preoperative values. When evaluating the affected renal function by split function (SF), the mean postoperative SF in the affected kidneys was significantly decreased compared to the preoperative value. In the LPNSRPC group, the mean postoperative GFR and SF in the affected kidneys were not significantly changed compared with the preoperative values. Conclusion: Our preliminary experience demonstrates that LPNSRPC facilitates maximal nephron-sparing surgery without collateral thermal damage causing renal impairment. <!--EndFragment-->